« Complejizar lo existente » : resistencias del sentido en la obra de Sergio Chejfec - Benoît Coquil (Cuadernos LIRICO, 2017)
This article aims to describe and clarify what appears to be in Sergio Chejfec’s work a reading difficulty and some resistance of the meaning. That hermeticism can in part be conceived as a generational refusal of some literature regarded as too limpid and normative, but it is also related to some of the author’s particular questions, such as the familiar memory and the Jewish identity. The impossible decipher – of signs and the reality – is a recurrent pattern, in his narrative fiction works and his essays. Finally this article proposes a brief typology of formal elements which in the narrative texts contribute to disrupt the linearity and the transmission of information – what Lambert Barthélémy calls « meandering effects ».